Occurrence record and range extension of Pomadasys andamanensis McKay & Satapoomin, 1994 (Heamulidae: Haemulinae) from Great Nicobar Island, India - Mrinal Kumar Das; Chandrakasan Sivaperuman (Journal of Fisheries, 2023)
Present study reports the occurrence of Andaman grunt, Pomadasys andamanensis McKay & Satapoomin, 1994 for the first time from Indian waters based on one specimen (standard length 156.27 mm) collected from Great Nicobar Island, Andaman and Nicobar Island. This finding represents a new addition to the grunt fish fauna of Andaman and Nicobar Island, India. The species is distinguished from its congeners by having four separated longitudinal black stripes on the dorsal half of the body. The detailed morphological features of P. andamanensis are provided and compared with its previous records. Description and figures of the species are provided herewith along the morphometric measurements and meristic counts.